2011
DOI: 10.1088/0264-9381/28/6/065009
|View full text |Cite
|
Sign up to set email alerts
|

Induced self-energy on a static scalar charged particle in the spacetime of a global monopole with finite core

Abstract: We analyze the induced self-energy and self-force on a scalar point-like charged test particle placed at rest in the spacetime of a global monopole admitting a general spherically symmetric inner structure to it. In order to develop this analysis we calculate the threedimensional Green function associated with this physical system. We explicitly show that for points outside the monopole's core the scalar self-energy presents two distinct contributions. The first one is induced by the non-trivial topology of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 33 publications
(100 reference statements)
0
16
0
Order By: Relevance
“…In [26], we have shown that the core-induced part in the self-energy above is finite for points away from the core. It remains to analyze the boundary-induced part for point near the boundary itself.…”
Section: Particle Inside the Boundarymentioning
confidence: 90%
See 4 more Smart Citations
“…In [26], we have shown that the core-induced part in the self-energy above is finite for points away from the core. It remains to analyze the boundary-induced part for point near the boundary itself.…”
Section: Particle Inside the Boundarymentioning
confidence: 90%
“…The above expressions for g l are reduced to the previously obtained ones in [26] for mR → ∞. The functions (2.41) and (2.42) obey DBC or NBC for r ′ = R and for r > = R, respectively.…”
Section: Particle Inside the Boundarymentioning
confidence: 92%
See 3 more Smart Citations